THE MEDIA AND PUBLIC ISSUES: A GUIDE FOR TEACHING CRITICAL MINDEDNESS (Authors: Kenneth Nixon & Walter Werner) - McCormick, Chris (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1992)
Kenneth Nixon & Walter Werner. THE MEDIA AND PUBLIC ISSUES: A GUIDE FOR TEACHING CRITICAL MINDEDNESS. London: The Althouse Press, 1990. 81 pp. 12.95.